Caring soils for sustainable land uses. Issue 5 (21st July 2020) - Ramos, Juan‐Luis; Lansac, Rocio
Summary: The aim of the article is to develop and explore the idea that soil health is an essential element in combating climate change and promoting food security. An important aspect of this is that soil, rather than simply serving to support plants and as a niche for animals and microbes, also functions as a natural reactor that, through a series of chemical and biological reactions, purifies water, replenish aquifers and maintains equilibria in surface waters. This topic is particularly timely given the recent announcement of the Mission program for Health of Soils by the European Commission. Within this realm, the article intends to catalyze and promote the debate around what defines sustainable agriculture in order to help shape its future.